The Function and Structure of the dm?(y)t “Myth” - Diamond, Kelly-Anne.
The title dm?(y)t refers to one of the dramatis personae in the early funerary cult drama, who helps with the transfiguration of the deceased in terms of the collecting and reassembling of the deceased’s bones or limbs. This term can be used in the singular and the plural and is derived from the root dm? “to collect or gather.” The title dm?(y)t may be translated as “bone or limb collector.” By the Fifth Dynasty there is evidence that the root dm? was directly associated with the reconstruction of Osiris’ body, yet the dm?(y)t is not part of the Osirian cult drama. Her presence may predate the superimposition of the Osirian characters, but there appears to be a clear association between the function of the dm?(y)t and the function of the goddess Isis in the Osirian myth. Did the canonization of this myth lead to Isis taking over the dm?(y)t’s function in the transfiguration of the deceased? Following the myth-ritual school, is the Osirian myth attempting to explain the role of the dm?(y)t in the funerary service by superimposing Isis? In light of more recent research on myth structure and development, following the work of Dr. Katja Goebs, this work attempts to contextualize the use of the dm?(y)t-character in ritual texts and illustrations. In an effort to pinpoint the mythical relationship and the structural relationship of the actors/objects, I endeavor to understand what makes the use of the dm?(y)t “myth” efficacious for the user.